DAMPAK RELOKASI PASAR STUDI KASUS DI PASAR SAMPANGAN KOTA SEMARANG - Susilo Endrawanti; Christine Diah Wahyuningsih (FEB UNTAG Semarang, 2014)
One means of trading in the town are the market, both traditional markets, semi modern markets and the modern markets. In the midst of the development of modern markets, and business franchises in major cities including Semarang as the capital city Central Java, where traditional markets are expected to be still exist. Therefore Semarang City Government adopted a policy to perform traditional market arrangement, being pushed by the modern market. Recently Sampangan Market has been relocated which is only approximately 1 km away from the site of the old market, it is expected to bring better impact than the Old Sampangan Market. From the above case, researchers were interested in examining the impact of the relocation of the market, the Case Study in Sampangan Market Semarang. Purposes of this study were: 1) To investigate the impact to the traders individually, 2) the impact to the traders (traders association), 3) the impact to the buyers, 4) the impact to the community around the market, 5) the impact to the market managers. The use of the study: 1) To examine the impact of the relocation of the market, 2) As the materials of information for the study of social science, 3) For the inputs to Dinas Pasar Kota Semarang in implementing government policies especially those related to the impact of the relocation of the market. The type of research is descriptive qualitative description one. Methods of data collection, observation, in-depth interviews with 10 informants consisting of merchants, traders associations, purchasers, and the public about markets. As a key person Researcher interviewed also Kepala Dinas Pasar and Kepala Pasar (market manager). The interpretation of the results of interviews with informants were used as an analysis of the data. The results of research and fact findings are: 1) The impact of individual modern semi market traders with zoning seemed to be clean, comfortable, safe, and yet not followed by significant increase in revenue due to customer’s reduce 2) From the grocery merchants that occupy the outskirts of building complained when it rains water wet (tampias,Jvneese) 3) On the other hand, profit are taken by the trader surrounding the market 4) Buyers are convenient in shopping, but the elder people can not meet the needs sold upstairs 5) With the zoning, market manager has broad responsibilities, but there are only 3 personnels consists of two collectiors and one security staff, so that less than the maximum in management, the control’s function in particular. In addition to the above, New Sampangan Market is not equipped with signposts showing the merchandise criteria so that buyers sometimes have to ask for the type of items sought. keywords: market, market relocation, market traders, impacts